Location and Season Interaction on Reproductive Phenotypic Traits and Blood Biochemical Profile of White Fulani Breeding Bulls under Smallholder Production System - Abdulsalam, W.; Egena, S.S.A.; Otu, B.O.; Alemede, I.C.; Sikiru, A.B. (Nigerian Journal of Animal Science, 2023)
On-field Animal Research at three locations within Southern Guinea Savannah Agroecological Zone of Niger State of Nigeria was implemented in dry and wet seasons. The experimental animals investigated are White Fulani bulls (n=1404) kept under smallholder production system. Body weights of bulls were determined using Shaeffer’s formula; the scrotal circumference and testicular length were measured. Body Condition Score (BCS) of the bulls was determined and rated on a 5-point scale (BCS=1-5). Testicular biometric measurements were used to categorize bulls into high and low fertile bulls. Blood samples were collected from 24 bulls from each of the category of fertility status established. There was significant p<0.05 interactions effects of location and seasons on live weight, body condition scores, scrotal circumference and testis length of the bulls (p<0.05). Average live weight of the bulls was higher p<0.05 during the wet season compared with dry season, 426.78±5.67 kg during wet season compared with 397.10±6.20 kg during the dry season. Overall, there were significant p<0.05 contributions of both location and season to the reproductive phenotypic traits of the breeding bulls. There were higher P<0.05 concentrations of blood biochemical parameters during the wet season compared with the dry season. However, compared with other locations, the concentrations of blood glucose, luteinizing hormones, testosterone, and cholesterol were significantly p<0.05 higher for the breeding bulls in Mokwa compared with other locations. There was significant (p<0.05) contributions of both the location and season interactions on blood biochemical parameters of the breeding bulls including the blood glucose, blood urea nitrogen, luteinizing hormone, testosterone and cholesterol concentration of the bulls. Similarly, high fertile bulls have higher (p<0.05) concentrations of blood urea nitrogen, testosterone and cholesterol compared with the low fertile bulls.